Noncontact optical displacement sensor using an adiabatic u-shaped tapered fiber - Ab Razak, Mohd Zulhakimi; Reduan, Siti Aisyah; Sharbirin, Anir Syazwan; Jamaludin, Norsyazriza; Zulkifli, Mohd Zamani; Ahmad, Harith (IEEE, 2015)
A simple noncontact displacement microfiber sensor using adiabatic U-shaped tapered fiber is proposed and demonstrated. The microfiber is fabricated using a systematic fiber flame brushing technique, where the fiber waist diameter is proportional to the duration of the heating cycles. The sensor is capable of measuring a wide displacement distance up to 12 mm. A sensitivity of 0.2 dB/mm is recorded at a minimum tapered diameter of 8 µm. In comparison with the previous works of using Fresnel reflection method, the results of our proposed method show significant improvement in sensing range, which is indicated by distinct inclination of the loss slope. The microfiber probe shows a promise for a sensitive sensing at low development cost.